Propriedades estáticas e dinâmicas de multicamadas magnéticas acopladas quasiperiodicamente - Machado, Leonardo Dantas (2009)
In this work we study, for two different growth directions, multilayers of nanometric magnetic metallic lms grown, using Fibonacci sequences, in such a way that the thickness of the non-magnetic spacer may vary from a pair of lms to another. We applied a phenomenological theory that uses the magnetic energy to describe the behavior of the system. After we found numerically the global minimum of the total energy, we used the equilibrium angles to obtain magnetization and magnetoresistance curves. Next, we solved the equation of motion of the multilayers to nd the dispersion relation for the system. The results show that, when spacers are used with thickness so that the biquadratic coupling is strong in comparison to the bilinear one, non usual behaviors for both magnetization and magnetoresistance are observed. For example, a dependence on the parity of the Fibonacci generation utilized for constructing the system, a low magnetoresistance step in low external magnetic fields and regions that show high sensibility to small variations of the applied field. Those behaviors are not present in quasiperiodic magnetic multilayers with constant spacer thickness